Effect of recasting procedure upon corrosion behavior and metallic ion release of Co-Cr-Mo dental alloy in physiological - Silva, Jose Wilson de Jesus [UNESP]; Baldissera, Silmara Cristina [UNESP]; Felipe, Hamilton de [UNESP]; Codaro, Eduardo Norberto [UNESP] (De Gruyter, 2009)
Recasting process influence upon corrosion behavior of Co-Cr-Mo dental alloy in simulated physiological serum has been investigated using chemical and electrochemical techniques. Recast Co-Cr-Mo alloy by induction (IND) or by blowtorch (FLAME) has exhibited similar dendritic structures. Both IND and FLAME alloys have presented good corrosion resistance in physiological serum. Passivation process provides this corrosion resistance. Codissolution makes this process difficult. Passive films, formed on these alloys, have been analyzed as a dual layer consisting of an inner barrier and an outer porous layer. Passive film protective characteristics are higher in FLAME than in IND alloy. On this last alloy, the passive film is more porous due to a higher Codissolution. ©Carl Hanser Verlag, München.
Keywords: Co-dissolution; CoCrMo alloy; Corrosion behavior; Dendritic structures; Dual layer; Electrochemical techniques; Ion release; Passivation process; Passive films; Porous layers; Protective characteristic; Body fluids; Chromium; Corrosion resistance; Corrosive effects; Dendrimers; Dental alloys; Flame resistance; Flammability; Molybdenum; Passivation; Molybdenum alloys